Oxidant and antioxidant enzyme response of redbine sweet sorghum under NaCl salinity stress (Bioagro, 2020)
Sorghum bicolor is an indispensable source of bioactive compounds with benefits to human health.  In present study, salt tolerance of Redbine variety of sweet sorghum was investigated via enzymatic and non-enzymatic antioxidants. Plants were supplied with Hoagland solution containing 0-200 mM salt concentrations for 10 days. Enzyme activities, chlorophyll and carotene contents were spectrophotometrically assessed. Root catalase (CAT), ascorbate peroxidase (APX), glutathione reductase (GR), and proline amounts indicated increase in 50-150 mM doses revealing the protective response of the plant. As distinct from other parameters, superoxide dismutase (SOD) activity and the amount of membrane lipid peroxidation (malondialdehyde, MDA) revealed increase in all concentrations both in roots and leaves. APX, GR, glutathione S-transferase (GST), MDA, and Proline in leaves and roots were similar with increasing trend. However, SOD activity was the highest at 200 mM salt concentration. Redbine sweet sorghum reacted by increasing the synthesis of all chlorophylls and carotene against all concentrations. The plant indicated an effective response against salt stress. Increasing salt concentrations caused increase in chlorophyll and carotene contents indicating the effective role of carotenes in plant defense against salt stress. Although the antioxidant enzyme activities of Redbine sweet sorghum contribute to its response to salt stress, the situation seems to be not adequate at higher concentrations.
Keywords: Malondialdehyde; proline; salt stress